The Mechanism of Consumer Premium Payments in Agricultural Live-Streaming under Dual Emotional Appeals: A Perspective on Warmth and Humour - Ziyi Zhou (International Journal of Social Sciences and Public Administration, 2026)
Against the backdrop of China's transition from poverty alleviation to rural revitalisation, agricultural live-streaming commerce has become an indispensable pathway for sustaining hard-won poverty reduction gains and advancing high-quality rural development. This paper adopts the Elaboration Likelihood Model (ELM) as its fundamental research framework, introduces emotional resonance and perceived entertainment value as mediating variables, and constructs a theoretical model examining the impact of different emotional appeals on consumers’ willingness to pay a premium for agricultural support live-streaming. An empirical analysis of the path relationships among these variables is also conducted.The results indicate that consumers’ perceived warmth and humour appeals both have a significant positive impact on willingness to pay a premium. Emotional resonance transmits the effect of perceived warmth on consumers' propensity to pay above-market prices, whereas perceived entertainment accounts for the indirect link between perceived humour and consumers' inclination toward premium-priced purchasing. Finally, based on the research findings, recommendations are provided for optimising emotional strategies in agricultural live-streaming.